2010
DOI: 10.1002/ijc.24737
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of Merkel cell virus in human tissues and possible mode of transmission

Abstract: Merkel Cell Virus (MCV) is a newly discovered polyomavirus, recently found in a rare skin cancer, Merkel cell carcinoma (MCC). However, MCV has also been detected in some normal tissue samples. We tested and compared the relative quantity of the MCV in a set of diverse human tissue samples with the MCC samples. The levels of MCV in MCCs were over 60 times higher than the highest values in all other tissues. Low quantities of MCV were detected in diverse tissue samples independently of malignant or benign histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
188
8
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(217 citation statements)
references
References 21 publications
18
188
8
3
Order By: Relevance
“…However, previous studies on the frequency of MCPyV infection in oral tumours or tumour-like lesions are partial and incomplete (7,15). High viral loads of MCPyV were detected in all saliva samples from 10 patients without cancer (7).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…However, previous studies on the frequency of MCPyV infection in oral tumours or tumour-like lesions are partial and incomplete (7,15). High viral loads of MCPyV were detected in all saliva samples from 10 patients without cancer (7).…”
Section: Introductionmentioning
confidence: 76%
“…The possibility of contamination was unlikely, as ultrapure water-negative controls were consistently negative. Loyo et al (7) reported data on MCPyV DNA prevalence in oral cavity fresh-frozen materials (51/67, 76%); the prevalence was 19/47 SCCs, 2/10 normal mucosal samples and 10/10 saliva samples from patients without cancer. Oral cavity samples had 0.026 copies/genome, while MCCs had an average of 10 copies/genome (range, 173-0.05 copies̸genome) and saliva had an average of 0.128 copies/genome (range, 5-0.01) (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MCPyV viral load on the skin surface varies from less than 1 copy per 1000 cells to 1000 copies per cell (9,26,30,(39)(40)(41). The mean DNA copy per cell in normal skin has been reported to be 0.02-0.07 (42).…”
Section: Detection Of the Viral Genomementioning
confidence: 99%